Investigating the Nexus of Corporate Social Responsibility and Brand Equity : A Systematic Review - Singh, Anupam; Verma, Priyanka (Prabandhan: Indian Journal of Management, 2017)
Corporate social responsibility (CSR) is a hot topic in the business nowadays. More than ever before, companies engage in socially responsible activities to make a positive contribution to society or their marketing goals. This phenomenon has led to increase in magnitude of research in this direction. This study is an endeavour to analyze and synthesize the findings of previous studies to arrive at a concrete conclusion on nexus of CSR and brand equity (BE). The methodology used in this study is ’systematic literature review’ by utilizing ’citation pearl growing’ technique in five widely known databases namely EBSCOS, Emerald Insight, Elsevier’s Science Direct, Google Scholar, and JSTOR. Findings, based on extensive literature review, revealed that CSR could fetch positive rewards for a firm in terms of improved brand image, loyalty, and purchase intention, which consequently strengthen the brand performance. Finally, after rigorous analysis on the current state of research in the field of CSR, a probable future research agenda was proposed, which may serve as a guideline for future investigators to decide the focus area, and for practitioners to design and implement appropriate strategies for the firm’s CSR.